THE DETERMINANTS OF PERFORMANCE OF SHARIA EQUITY MUTUAL FUNDS - Meidiana Rizki Adelia; Muhammad Nafik Hadi Ryandono (Jurnal Ekonomi Syariah Teori dan Terapan, 2020)
There are a lot of factors that determine the sharia equity mutual funds performance, included stock selection skill, market timing ability, and fund age. This study aims to understand the effect of stock selection skill, market timing ability, and fund age on the sharia equity mutual funds performance in Indonesia from 2012 to 2018. This research uses a quantitative approach using an explanatory research type. The sampling technique in this study was purposive sampling and 6 sharia equity mutual funds were selected as samples. This study uses multiple linear regression analysis. The result of the study displayed that stock selection skill and market timing ability have a significant effect on the performance of sharia equity mutual funds in Indonesia from 2012 to 2018. On the contrary, fund age have no effect on the performance of sharia equity mutual funds in Indonesia from 2012 to 2018. Keywords: stock selection skill, market timing ability, fund age, sharia equity mutual funds perfomanceREFFERENCE Abdalloh, I. (2018). Pasar modalsyariah. Jakarta: Elex MediaKomputindo.Andriani, L. F., & Mawardi, W.(2018). Analisispengaruh stockselection skill,market timingability, total assetdan expenseratio terhadap kinerjareksa dana syari'ah di IndonesiaPeriode 2013 - 2016. DiponegoroJournal of Accounting, 7(4), 1-10.Anjani, B. B., (2012) Analisis faktor-faktoryang berpengaruh terhadapkeputusan investasi padaperusahaan food and beveragesdi Bursa Efek Indonesia.Diponegoro Journal of Accounting,8(5), 1-15.Bank Indonesia. Tingkat imbal hasilSertifikat Bank IndonesiaSyariah (SBIS).Diakses melaluiwww.bi.go.idtanggal 17Desember 2019Az-Zuhaili, W. (1997). Al-fiqh al-islami waadillatuhu, juz 4. Damaskus: Dar AlFikr.Darmadji, T., & Fakhruddin, H. M. (2001).Pasar modal di Indonesia:Pendekatan tanya jawab. Jakarta: SalembaEmpat.Departemen Agama, R. I. (2010). Alqur’andan tafsirnya. Jakarta:LenteraAbadi.Ghozali, I. (2012). Aplikasi analisismultivariatdengan programIBM SPSS 20, edisikeenam. Semarang: UniversitasDiponegoro.Gregory, A., J. Matatko dan R. Luther. (1997). Etchical unit trust financialperformance: Small companyeffect and fund size effect. Journal of Bussiness FinanceandAccounting 24(5), 705-725.Hamzah, A., & Yohanes, A. (2014). Analisisperbandingan kinerja reksa danasyariah dengan reksa danakonvensional jenis saham padaperiode 2008-2012. MIX: JurnalIlmiah Manajemen, 4(3), 396-409.Hasbi, Hariandy. 2010. Kinerja reksadanasyariah tahun 2009 diIndonesia. Jurnal Keuangan danPerbankan, 14(1), 62-73.Hidayat, Taufik, S. E., & Si, M. (2011). Bukupintar investasi syariah. Jakarta:Mediakita.Indrawati, U., & Wahono, B. (2017).Pengaruh market timing dan stockselection terhadap kinerja reksadana di indonesia (studi kasuspada reksa dana saham periode2013-2015). Jurnal Ilmiah Riset Manajemen, 6(4), 101-113.Jakarta Islamic Index. Index Bulanan JII(Jakarta Islamic Index). Diaksesmelaluiwww.finance.yahoo.comtanggal 15 Desember 2019 Nguyen, A.-N., Shahid, M. S., & Kernohan,D.(2018). Investor confidenceandmutual fund performance inemerging markets: InsightsfromIndia and Pakistan. Journal ofEconomic Studies, 45(6), 1288-1310.Otoritas Jasa Keuangan. (2019). Laporanperkembangan pasar modalsyariah tahun 2018. Jakarta:Otoritas Jasa Keuangan._______. (2019). Statistikreksadana syariah desembertahun 2018. Jakarta: Otoritas JasaKeuangan._______. (2019). PeraturanOtoritas Jasa Keuangan Nomor19/POJK.4/2015 Pasal 21 tentangPenerbitan dan Persyaratantentang Reksa Dana Syariah_______. (2017). PeraturanOtoritas Jasa Keuangan Nomor35/POJK.04/2017 Pasal 2 tentangEfek dan Kriteria dalam Daftar EfekSyariah. Jakarta: Otoritas JasaKeuangan._______. Nilai Aktiva Bersih(NAB) Reksadana Syariah. Diaksesmelalui www.reksadana.ojk.go.idtanggal 20 Desember 2019Rachmah, D. A., & Juniar, A. (2018).Analisispengaruh stock selectionskill,market timing ability, danfundlongevity terhadap kinerjareksadana saham syariah.Jurnal SainsManajemenKewirausahaan, 2(1),61–69.Rahardja, P., & Manurung, M. (2008). Teoriekonomi makro: Suatu pengantar,edisi keempat. Buku Seri TeoriEkonomi. Jakarta: Lembaga PenerbitFakultas Ekonomi UniversitasIndonesia. Robertson, G. (2002). Review Kinerja.Lokakarya Revie Kinerja. BPKP danExecutive Education, 47.Ryandono, Muhammad Nafik Hadi. (2009). Bursa efek daninvestasi syariah. Jakarta: SerambiIlmu Semesta.Sabila, F. H. (2019). Stock selection danmarket timing ability reksa danasyariah saham di Indonesia. Journalof Economic, Public, andAccounting (JEPA),1(2), 68–81.Sari, A. P. N., & Purwanto, A. (2012). Analisiskebijakan alokasiaset, kinerjamanajer investasidan tingkat risiko terhadapkinerja reksadana saham diIndonesia. Diponegoro Journal ofAccounting, 1(1) : 1-14. Sari, M. M., Mulyati, S., & Widarwati, E.(2019). Pengaruh stock selectionskill, market timing ability, turnoverratio dan cash flow terhadapkinerja reksa dana syariah.TSARWATICA (Islamic Economic,Accounting, and ManagementJournal), 1(01), 45–55.Satrio, Y., & Mahfud, M. K. (2016). Analisispengaruh total asset, fund age,expense ratio, dan portofolioturnover terhadap kinerja reksadana periode 2012-2014.Diponegoro Journal of Accounting,5(2) : 1-9.Syahid, N., & Arfinto, E. D. (2015). Analisispengaruh stock selection skill,market timing ability, fundlongevity, fund cash flow danfund size terhadap kinerja reksadana (studi kasus: reksadanasaham periode tahun2010-2014).Diponegoro Journal of Accounting,4(4) : 1-11.Syekh, B. H. H. A., & Halim, A. (2006). Tafsiral-ahkam. Jakarta: KencanaPrenada Media Group.Tandelilin, E. (2010). Portofolio dan iInvestasi:Teori dan aplikasi. Yogyakarta: Kanisius.Tversky, A., & Kahneman, D. (1979).Prospect theory: An analysis ofdecision underrisk. Econometrica,47(2), 263-291.Virlics, A. (2013). Investment decisionmaking and risk. ProcediaEconomics andFinance, 6,169-177.Waelan, W. (2008). Kemampuan memilihsaham dan market timing manajerinvestasi reksa dana saham diBursa Efek Indonesia. IndonesianJournal of Accounting andAuditing, 12(2), 167-176.Winingrum, E. P., & Pangestuti, I. R. D.(2011). Analisis stock selection skills,market timing ability, size reksadana, umur reksa dana danexpense ratioterhadap kinerjareksa dana saham yang terdaftardi Bursa Efek Indonesiaperiode Tahun 2006-2010. Skripsi tidak diterbitkan. Semarang: Universitas Diponegoro.